Association between multidimensional frailty and quality of life in older adults with coronary heart disease: a cross-sectional study - Mei, Dongmei; Yang, Yan; Meng, Defang; Hu, Yaoy; Wang, Xiaoyan (Frontiers in Psychology, 2025)
PurposeThis study aims to investigate the relationship between multidimensional frailty and quality of life among older adults with coronary heart disease who are hospitalized.Patients and methodsA convenience sampling approach was employed to select older adults with coronary heart disease admitted to the Cardiology Department of a tertiary hospital in Wuxi City between September 2023 and June 2024. The study utilized the General Information Questionnaire, the Tilburg Frailty Indicator (TFI), and the SF-12 Scale to gather data. To examine the relationship between multidimensional frailty and quality of life, Spearman correlation analysis was conducted. Additionally, stratified regression analysis was performed to identify factors associated with quality of life.ResultsAmong 254 older adults with coronary heart disease, 135 (53.15%) exhibited multidimensional frailty. The physical health score of frail older patients with coronary heart disease (36.62 ± 6.51) was found to be lower than that of their non-frail counterparts (42.88 ± 6.91). A negative correlation was observed between multidimensional frailty and quality of life, encompassing both physical and mental health aspects (r = −0.513, −0.428, p < 0.01). Further analysis using stratified regression revealed that multidimensional frailty independently accounted for 9.1 and 11.3% of the variance in quality of life (physical health and mental health, respectively) among older adults with coronary heart disease.ConclusionOlder adults with coronary heart disease often experience widespread frailty, which is linked to their quality of life. The presence of multifaceted weakness serves as a crucial indicator of life quality in these individuals.